2017
DOI: 10.15446/dyna.v84n202.56542
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on slurry erosion behavior of HVOF sprayed coatings

Abstract: Este trabajo investiga el comportamiento del desgaste en mezclas erosivas de recubrimientos depositados mediante la técnica de proyección térmica usando el proceso HVOF. Se analizaron tres tipos de recubrimientos, WC-CoCr con estructura de grano fino, Cr3C2-NiCr 75-25 y NiCrWSiFeB, estos últimos con tamaños de grano convencional. Los ensayos de desgaste erosivo se desarrollaron usando un tribómetro de recipiente de mezclas para evaluar la resistencia a la erosión de los recubrimientos a velocidades de impacto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…According to Reyes et al, the metallic binder is relatively soft and it is easy to erode it than the hard carbide particles. They suggested that as-sprayed specimens with lower surface roughness and higher microhardness have lower erodent penetration than those with higher surface roughness [42].…”
Section: Sem/eds Analysismentioning
confidence: 99%
“…According to Reyes et al, the metallic binder is relatively soft and it is easy to erode it than the hard carbide particles. They suggested that as-sprayed specimens with lower surface roughness and higher microhardness have lower erodent penetration than those with higher surface roughness [42].…”
Section: Sem/eds Analysismentioning
confidence: 99%
“…As discussed previously, some unmolten TiC particles were also noted in the coating, which could have contributed to higher surface roughness, suggesting need for further feedstock and process optimization. However, it is also pertinent to mention that the surface roughness of the SPS-processed Cr 3 C 2 coating in this work was lower than that previously reported for HVOF-processed Cr 3 C 2 -based coating [19]. For wear application, it is desirable to produce coatings with low surface roughness.…”
Section: Resultsmentioning
confidence: 73%
“…However, in conventional Ni-Cr coating, it was observed that there was an increase in weight loss with increase in sand particle size and duration of the test showed good cavitation erosion resistance [20,113]. Nanostructured WC-based and Cr3C2-25NiCr coating showed low erosion-corrosion and erosion-wear compared to conventional coatings corresponding to highest microhardness value, lower porosity, higher fracture toughness, and lower roughness [6,19,21]. The nano carbide ceramic phase mainly causes wear resistance while the corrosion resistance is provided by the binder phase NiCr matrix of the nanostructured Cr3C2-25NiCr cermet coatings [73,83,103].…”
Section: Aisi 1018 Steel Erosion Corrosion Test Potentiodynamic Polarmentioning
confidence: 98%